(untitled) (Al-Aasar, 2025)
This research paper explores Iqbal’s vision of resilience (istiqāmat), renewal (tajdīd), and global transformation, highlighting its intellectual depth and contemporary relevance. Iqbal considered resilience not merely as patience or endurance but as a dynamic spiritual force that strengthens the self (khudī), enabling individuals and nations to remain steadfast in pursuit of higher ideals. Renewal, in Iqbal’s thought, emerges as the process of reinterpreting Islamic teachings in light of modern challenges, fostering creativity and intellectual vitality without breaking from the roots of revelation. Global transformation, as envisioned by Iqbal, transcends geographical, racial, and cultural boundaries, projecting Islam’s universal message of justice, equality, and spiritual awakening for all humanity. The study analytically examines how Iqbal integrates these three concepts into a coherent framework that addresses both individual development and collective progress. His emphasis on spiritual selfhood, ethical consistency, and intellectual dynamism provides a roadmap for Muslims to overcome stagnation and reclaim their role in shaping global civilization. Furthermore, the paper highlights the significance of Iqbal’s thought in the contemporary context, where political instability, materialism, and cultural fragmentation continue to challenge human societies. By analyzing Iqbal’s philosophical and poetic works, this paper argues that his vision is not limited to literary appreciation but constitutes a practical program for personal, social, and global reform. His call for resilience, renewal, and universal brotherhood remains highly relevant in the 21st century, offering hope for peace, justice, and sustainable development. In addition to its analytical dimension, this study emphasizes that Iqbal’s vision is deeply action-oriented. His concept of istiqāmat (resilience) calls upon individuals to resist despair and inertia, while tajdīd (renewal) demands creative reinterpretation of faith in light of ever-changing contexts. For Iqbal, these two principles are inseparable, as resilience without renewal can lead to rigidity, while renewal without resilience may result in superficiality or loss of authenticity. Moreover, the paper contends that Iqbal’s philosophy offers an integrative model for addressing crises of identity, leadership, and morality in the Muslim world and beyond. His global outlook does not confine itself to one nation or culture but rather envisions a spiritually enriched civilization capable of guiding humanity toward justice and peace. This universal dimension underscores the timeless applicability of his thought. Ultimately, the research underscores that Iqbal’s legacy provides both a theoretical framework and a practical manifesto for transformation. His ideas continue to inspire intellectual inquiry and socio-political reform, making his philosophy an enduring resource for addressing the pressing challenges of modernity while remaining firmly rooted in the spiritual heritage of Islam.